Pharmacokinetic-pharmacodynamic modelling for the determination of optimal dosing regimen of florfenicol in Nile tilapia (Oreochromis niloticus) at different water temperatures and antimicrobial susceptibility levels - Rairat, Tirawat (Journal of fish diseases, 2019)
© 2019 John Wiley & Sons Ltd.